Real-Time Sequencing To Decipher the Molecular Mechanism of Resistance of a Clinical Pan-Drug-Resistant Acinetobacter baumannii Isolate from Marseille, France - Rolain, Jean-Marc; Diene, Seydina M.; Kempf, Marie; Gimenez, Gregory; Robert, Catherine; Raoult, Didier (Antimicrobial Agents and Chemotherapy, 2013)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC